Pengaruh Resiko Kredit, Likuiditas, Efisiensi Operasional dan Tingkat Ekonomi Makro Ekonomi Terhadap Kinerja Bank Pembangunan Daerah di Pulau Sumatera - Verawaty Verawaty; Ade Kemala Jaya; Yolanda Widiati (Universitas Muhammadiyah Metro, 2017)
The purpose of this study was to obtain the empirical evidence about the effect of credit risk, liquidity, operational efficiency and the macro-economic level to the the performance of regional development banks. This study population was eight Regional Development Banks in Sumatera Island during 2011-2014. Analysis technique used is multiple linear regression. The results showed simultaneously, all the independent variables affected the dependent variable. Partially, only credit risk and efficiency negatively affected the performance of the bank. Liquidity and macro-economic level did not have positive influence on the bank's performance. Keywords: the performance of banks, credit risk, liquidity, operational efficiency and macro-economic level